VO.12 – Approval of unit rates of non-schedule Item water proofing works at foundation - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the VO.12 – approval of unit rates of non-schedule Item water proofing works at foundation of BRACU new campus project site.